2020
DOI: 10.1016/j.nicl.2020.102360
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural changes in the reward system are associated with post-stroke depression

Abstract: Highlights Depressed stroke survivors exhibit abnormal frontal and subcortical structural connectivity. Microstructural changes resemble those reported in major depressive disorder. Subnetworks linked with reward processing are associated with poststroke depression. Localized tractography confirmed involvement of connections in these networks. Grey matter volume, fractional anisotropy and free-water collectively predic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…Associations of WMHs with PSD varied according to the type of WMH and the time after stroke, such that early depressive symptoms are associated with periventricular WMHs and delayed severe depression rather with diffuse WMHs [ 172 ]. Poststroke depression (PSD) was also shown to be associated with gray matter volume loss, reduced fractional anisotropy, and increased extracellular free water (FW) in the reward system, similar to features observed in LLD without stroke [ 173 ]. One recent study reported infarcts in the right amygdala and striatum, and disconnection of right limbic and fronto–cortico–basal ganglia–thalamic circuits associated with PSD [ 174 ], while others suggested that generalized degenerative and vascular brain pathology rather than lesion-related pathology may be an important predictor for PSD [ 175 ].…”
Section: Structural Brain Lesions In Vadmentioning
confidence: 99%
“…Associations of WMHs with PSD varied according to the type of WMH and the time after stroke, such that early depressive symptoms are associated with periventricular WMHs and delayed severe depression rather with diffuse WMHs [ 172 ]. Poststroke depression (PSD) was also shown to be associated with gray matter volume loss, reduced fractional anisotropy, and increased extracellular free water (FW) in the reward system, similar to features observed in LLD without stroke [ 173 ]. One recent study reported infarcts in the right amygdala and striatum, and disconnection of right limbic and fronto–cortico–basal ganglia–thalamic circuits associated with PSD [ 174 ], while others suggested that generalized degenerative and vascular brain pathology rather than lesion-related pathology may be an important predictor for PSD [ 175 ].…”
Section: Structural Brain Lesions In Vadmentioning
confidence: 99%
“…The current work included data drawn from the STROKDEM (Study of Factors Influencing Posttroke Dementia) 10 and 3 studies from the STROKOG consortium, including the DEDEMAS (Determinants of Dementia After Stroke) cohort from Germany, 11 the SSS (Sydney Stroke Study) from Australia, 12 and STRATEGIC from the United Kingdom. 13 Four other studies from Hong Kong, Korea, and Singapore contributed data; however, the MR images did not pass quality control and were excluded from the analyses. Images were required to have slice thickness <5 mm to allow accurate brain structures segmentation.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed acquisition parameters for these structural sequences have been published previously. 19 Rs-fMRI was acquired with an echo-planar imaging sequence using the following parameters: TR = 2000 ms, TE = 30 ms, flip angle = 75°, slice thickness = 3 mm and gap = 0.3 mm. Images were acquired in the axial plane with FOV = 211 × 211 mm 2 , matrix size = 64 × 64 mm 2 and number of slices = 40.…”
Section: Methodsmentioning
confidence: 99%